A durable seawater desalination membrane and preparation method thereof
The preparation of durable seawater desalination films using modified MoS2/ZIF-8 composite materials and modified hyperbranched polyethers solves the problems of existing membrane pollution and poor durability, achieving higher anti-pollution and antibacterial properties, extending service life and reducing costs.
Patent Information
- Application Number
- CN202411562102.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing seawater desalination membranes have serious membrane pollution and poor durability in practical applications, resulting in shortening of service life and increasing seawater desalination costs.
Modified MoS2/ZIF-8 composite material and modified hyperbranched polyether were used as the main raw materials, ZIF-8 was synthesized by hydrothermal method, and MoS2 nanosheets were coated on its surface, and the surface of silane coupling agent was modified, and the cast film liquid was formed and coated on the non-woven fabric. After multiple solutions, a durable seawater desalination film was formed.
It improves the anti-pollution and antibacterial properties of the membrane, significantly extends the service life of the membrane, reduces the cost of seawater desalination, and maintains efficient water flux and desalination rate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of seawater desalination membranes, and in particular to a durable seawater desalination membrane and a preparation method thereof. Background Art
[0002] With the rapid development of the economy and society and the growing demand for water, the global water resources and energy shortage problem is becoming increasingly severe. Membrane separation technology has been widely used in the fields of seawater desalination and sewage treatment due to its advantages of low energy consumption, high efficiency, economy and environmental protection. As the most advanced desalination membrane, polyamide thin-layer composite membrane has been widely used in nanofiltration, reverse osmosis and forward osmosis membrane separation processes. However, in actual application, composite membranes face serious membrane pollution and poor durability, which shortens the service life of the membrane and ultimately increases the cost of seawater desalination. Therefore, the development of durable and anti-pollution composite membranes has always attracted people's attention.
[0003] The improvement of the durability of desalination membranes can also improve the durability of desalination membranes.
[0004] The anti-fouling modification of membranes generally focuses on two aspects: (1) Hydrophilic modification of membrane surface: The better the hydrophilicity of the membrane, the stronger the interaction between the membrane and water, the less likely pollutants are to accumulate on the surface of the membrane to cause pollution, and the better the anti-fouling ability. The method of hydrophilic modification of membrane surface is mainly to introduce hydrophilic substances into the membrane body or surface, such as: zwitterions, hydrophilic nanoparticles, or substances rich in amine, carboxyl, and hydroxyl groups. (2) Antibacterial modification of membrane surface: The better the antibacterial performance of the membrane surface, the more effectively it can inhibit the reproduction of bacteria on the membrane surface, thereby significantly improving the membrane's anti-biological fouling performance. The method of antibacterial modification of membranes is mainly to introduce antibacterial substances into the membrane body or surface, such as: silver or copper nanoparticles, chitosan, quaternary ammonium salts, etc. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a durable seawater desalination membrane and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a durable seawater desalination membrane comprises the following steps:
[0008] Step S1, after mixing and stirring 15-20wt% polysulfone, 2-4wt% modified MoS2 / ZIF-8 composite material and 70-90wt% N,N-dimethylformamide for 10-30min, adjusting the system temperature to 120-130°C, heating and stirring for 5-10h, and then standing for 24h to form a casting solution, and then evenly coating the casting solution on a non-woven fabric, and then immersing it in water to obtain a base film;
[0009] Step S2, immersing the base membrane in the aqueous solution and the oil phase solution in turn for 1.5-2.5 minutes each, and then rinsing with deionized water for 10 minutes to obtain a seawater desalination membrane;
[0010] Furthermore, the aqueous phase solution in step S2 is prepared by mixing and stirring 2-3wt% of m-phenylenediamine, 0.5-1wt% of modified hyperbranched polyether, 0.1-0.5wt% of modified MoS2 / ZIF-8 composite material, 2-5wt% of isopropanol, 0.01-0.05wt% of sodium hydroxide and deionized water;
[0011] Furthermore, the oil phase solution in step S2 is prepared by mixing and stirring 0.15-0.3 wt % of trimesoyl chloride, 1-3 wt % of toluene, 5-8 wt % of anisole and deionized water.
[0012] The modified hyperbranched polyether is prepared by the following steps:
[0013] Step A1, adding pentaerythritol and potassium hydroxide into a reactor, raising the system temperature to 90-110° C. under stirring conditions, then introducing nitrogen, continuing to raise the temperature to 120-130° C., adding propylene oxide and stirring to react for 2-3 hours, after the reaction is completed, adding ethylene oxide, and controlling the system temperature to 110-120° C. and continuing to stir and react for 4-5 hours, after the reaction is completed, a hyperbranched polyether is obtained;
[0014] Step A2, adding a hyperbranched polyether and ethyl 2-aminoacetate into a reactor and stirring and mixing uniformly, then adding potassium hydroxide and stirring uniformly, introducing nitrogen, and raising the system temperature to 125-135° C. to react for 3-4 hours, and then raising the system temperature to 140-150° C. to continue the reaction for 4-5 hours. After the reaction is completed, maintaining the system temperature, vacuum treating for 40-60 minutes, adding phosphoric acid for neutralization, and adding magnesium silicate to remove salt substances, thereby obtaining a modified hyperbranched polyether;
[0015] Further, in step A1, the usage ratio of pentaerythritol, potassium hydroxide, propylene oxide and ethylene oxide is 0.01-0.03 mol: 0.05-0.15 g: 0.04-0.12 mol: 0.16-0.48 mol;
[0016] Furthermore, in step A2, the molar ratio of the hyperbranched polyether to ethyl 2-aminoacetate is 0.15-0.3:0.1-0.12, and the amount of potassium hydroxide used is 0.2-0.3% of the total mass of the reactants added.
[0017] The modified MoS2 / ZIF-8 composite material is prepared by the following steps:
[0018] Step B1, zinc nitrate hexahydrate and 2-methylimidazole were added to 30 mL of methanol and mixed evenly, respectively recorded as solution 1 and solution 2, then solution 1 and solution 2 were mixed and stirred for 2 h, ultrasonicated for 1 h, transferred to an autoclave, reacted at 90 ° C for 5-7 h, cooled to room temperature, centrifuged, washed, and dried to obtain ZIF-8;
[0019] Step B2, adding ZIF-8, ammonium molybdate and thiourea into deionized water and stirring evenly, transferring to an autoclave, reacting at 150-200°C for 5-10h, cooling to room temperature, centrifuging, washing, drying, collecting the product, and calcining at 500-700°C for 1-3h to obtain a MoS2 / ZIF-8 composite material;
[0020] Step B3, add MoS2 / ZIF-8 composite material to the mixed solution of deionized water and ethanol, adjust the system pH to 4, ultrasonically treat for 30 minutes, then add γ-aminopropyltriethoxysilane, condense and reflux at 40-60°C for 6 hours, and after the reaction is completed, reduce pressure and filter, wash and dry to obtain the modified MoS2 / ZIF-8 composite material;
[0021] Further, in step B1, the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 0.3-0.9:0.65-1.95;
[0022] Further, in step B2, the mass ratio of ZIF-8, ammonium molybdate, thiourea and deionized water is 0.5-2:1:1-3;
[0023] Furthermore, in step B3, the mass ratio of the MoS2 / ZIF-8 composite material, γ-aminopropyltriethoxysilane, deionized water and ethanol is 1:0.0025-0.04:50:10.
[0024] In a second aspect, the present invention also includes a durable seawater desalination membrane prepared by the above preparation method.
[0025] Beneficial effects of the present invention:
[0026] The invention uses pentaerythritol as an initiator, propylene oxide and ethylene oxide as the synthetic raw materials of the polyether segment, synthesizes a hyperbranched polyether containing terminal hydroxyl groups under the action of a catalyst hydrogen oxidizing agent, and then utilizes the terminal hydroxyl groups in the hyperbranched polyether to undergo an ester exchange reaction with the ester group in 2-aminoethyl acetate to synthesize a modified hyperbranched polyether containing a terminal amino structure. A ZIF-8 material is synthesized by a hydrothermal method, and a MoS2 nanosheet with a stable layered structure is coated on its surface to obtain a MoS2 / ZIF-8 composite material, and then a silane coupling agent is used to perform surface modification to obtain a modified MoS2 / ZIF-8 composite material. Finally, polysulfone and a modified MoS2 / ZIF-8 composite material are used as main raw materials, and a casting liquid is formed and coated on a nonwoven fabric to obtain a base film, and then the base film is sequentially immersed in an aqueous phase solution and an oil phase solution to form a polyamide film layer on the surface of the base film to obtain a final durable seawater desalination membrane.
[0027] The modified MoS2 / ZIF-8 composite material prepared by the present invention has excellent dispersibility and can be more evenly dispersed in the base film and the polyamide film layer, so that they can participate in the reaction more fully, and the composite material forms a cross-linked porous structure and also improves the water flux of the film layer; wherein, the ZIF-8 synthesized by a hydrothermal method has a large specific surface area and porosity, which can effectively increase the amount of water molecules passing through the film layer, and its surface is coated with MoS2 nanosheets with a layered structure, which has a high water flux and salt ion retention rate, because the pores in the MoS2 nanosheets present an hourglass-shaped geometry, and the MoS2 nanosheets can maintain excellent chemical stability and non-toxicity in water, thereby improving the durability of the film layer; the ZIF-8 in the composite material can also release Zn 2+ , Zn 2+ It also has good antibacterial ability and can penetrate the bacterial cell membrane, causing the physiological function of the bacteria to be disrupted and leading to bacterial death, thereby improving the antibacterial properties of the membrane surface and effectively inhibiting the reproduction of bacteria on the membrane surface, thereby significantly improving the membrane's anti-biological fouling performance and improving the durability of the membrane.
[0028] The modified hyperbranched polyether prepared by the present invention utilizes the terminal amino structure contained in the modified hyperbranched polyether to participate in the synthesis of the polyamide membrane layer. The large number of hydrophilic ether bonds contained in the modified hyperbranched polyether significantly improve the hydrophilicity of the membrane surface, and the improvement of the hydrophilicity enhances the interaction between the membrane and water molecules, which results in that pollutants in seawater are not easily accumulated on the membrane surface, the anti-pollution ability is improved, and the durability is improved; in addition, the unique branched structure and void structure of the modified hyperbranched polyether enable the membrane layer structure to be relatively loose when participating in interfacial polymerization, thereby improving the water flux of the membrane layer without changing the desalination rate. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1, the modified hyperbranched polyether is prepared by the following steps:
[0031] Step A1, 0.01 mol of pentaerythritol and 0.05 g of potassium hydroxide were added to a reactor, the system temperature was raised to 90° C. under stirring conditions, nitrogen was then introduced, the temperature was further raised to 120° C., 0.04 mol of propylene oxide was added, and the reaction was stirred for 2 h. After the reaction was completed, 0.16 mol of ethylene oxide was added, and the system temperature was controlled to 110° C. and the reaction was continued with stirring for 4 h. After the reaction was completed, a hyperbranched polyether was obtained;
[0032] Step A2, 0.15mol of hyperbranched polyether and 0.1mol of ethyl 2-aminoacetate are added to a reactor and stirred to mix evenly, potassium hydroxide is added and stirred evenly, nitrogen is introduced, and the system temperature is increased to 125°C for reaction for 3h, and then the system temperature is increased to 140°C, and the reaction is continued for 4h. After the reaction is completed, the system temperature is maintained, vacuum treatment is performed for 40min, phosphoric acid is added for neutralization, and magnesium silicate is added to remove salt substances to obtain a modified hyperbranched polyether, and the amount of potassium hydroxide is 0.2% of the total mass of the reactants added.
[0033] The modified MoS2 / ZIF-8 composite material was prepared by the following steps:
[0034] Step B1, 0.3 g zinc nitrate hexahydrate and 0.65 g 2-methylimidazole were added to 30 mL methanol and mixed evenly, respectively recorded as solution 1 and solution 2, then solution 1 and solution 2 were mixed and stirred for 2 h, ultrasonicated for 1 h, transferred to an autoclave, reacted at 90 ° C for 5 h, cooled to room temperature, centrifuged, washed, and dried to obtain ZIF-8;
[0035] Step B2, 0.5 g ZIF-8, 1 g ammonium molybdate and 1 g thiourea were added to deionized water and stirred evenly, then transferred to an autoclave, reacted at 150° C. for 5 h, cooled to room temperature, centrifuged, washed, dried, collected the product, and calcined at 500° C. for 1 h to obtain a MoS2 / ZIF-8 composite material;
[0036] Step B3, add 1g of MoS2 / ZIF-8 composite material to a mixture of 50g of deionized water and 10g of ethanol, adjust the system pH to 4, ultrasonically treat for 30min, then add 0.0025g of γ-aminopropyltriethoxysilane, condense and reflux at 40°C for 6h, after the reaction is completed, reduce pressure and filter, wash and dry to obtain a modified MoS2 / ZIF-8 composite material.
[0037] Example 2, the modified hyperbranched polyether is prepared by the following steps:
[0038] Step A1, 0.02 mol of pentaerythritol and 0.1 g of potassium hydroxide were added to a reactor, the system temperature was raised to 100° C. under stirring, nitrogen was then introduced, the temperature was further raised to 125° C., 0.08 mol of propylene oxide was added, and the reaction was stirred for 2.5 h. After the reaction was completed, 0.32 mol of ethylene oxide was added, and the system temperature was controlled to 115° C. and the reaction was continued with stirring for 4.5 h. After the reaction was completed, a hyperbranched polyether was obtained;
[0039] Step A2, 0.25mol of hyperbranched polyether and 0.1mol of ethyl 2-aminoacetate are added to a reactor and stirred to mix evenly, potassium hydroxide is added and stirred evenly, nitrogen is introduced, and the system temperature is increased to 130°C for reaction for 3.5h, and then the system temperature is increased to 145°C, and the reaction is continued for 4.5h. After the reaction is completed, the system temperature is maintained, vacuum treatment is performed for 50min, phosphoric acid is added for neutralization, and magnesium silicate is added to remove salt substances to obtain a modified hyperbranched polyether, and the amount of potassium hydroxide is 0.25% of the total mass of the reactants added.
[0040] The modified MoS2 / ZIF-8 composite material was prepared by the following steps:
[0041] Step B1, 0.6 g zinc nitrate hexahydrate and 1.3 g 2-methylimidazole were added to 30 mL methanol and mixed evenly, respectively recorded as solution 1 and solution 2, then solution 1 and solution 2 were mixed and stirred for 2 h, ultrasonicated for 1 h, transferred to an autoclave, reacted at 90 ° C for 6 h, cooled to room temperature, centrifuged, washed, and dried to obtain ZIF-8;
[0042] Step B2, 1 g ZIF-8, 1 g ammonium molybdate and 2 g thiourea were added to deionized water and stirred evenly, then transferred to an autoclave, reacted at 180°C for 7 h, cooled to room temperature, centrifuged, washed, dried, collected the product, and calcined at 600°C for 2 h to obtain a MoS2 / ZIF-8 composite material;
[0043] Step B3, add 1g of MoS2 / ZIF-8 composite material to a mixture of 50g of deionized water and 10g of ethanol, adjust the pH of the system to 4, ultrasonically treat for 30min, then add 0.01g of γ-aminopropyltriethoxysilane, condense and reflux at 50°C for 6h, after the reaction is completed, reduce pressure, filter, wash and dry to obtain a modified MoS2 / ZIF-8 composite material.
[0044] Example 3, the modified hyperbranched polyether is prepared by the following steps:
[0045] Step A1, 0.03 mol of pentaerythritol and 0.15 g of potassium hydroxide were added to a reactor, the system temperature was raised to 110° C. under stirring, nitrogen was introduced, the temperature was further raised to 130° C., 0.12 mol of propylene oxide was added, and the reaction was stirred for 3 h. After the reaction was completed, 0.48 mol of ethylene oxide was added, and the system temperature was controlled to 120° C. and the reaction was continued with stirring for 5 h. After the reaction was completed, a hyperbranched polyether was obtained;
[0046] Step A2, 0.3 mol of hyperbranched polyether and 0.12 mol of ethyl 2-aminoacetate are added to a reactor and stirred to mix evenly, potassium hydroxide is added and stirred evenly, nitrogen is introduced, and the system temperature is increased to 135 ° C. for reaction for 4 hours, and then the system temperature is increased to 150 ° C. and the reaction is continued for 5 hours. After the reaction is completed, the system temperature is maintained, vacuum treatment is performed for 60 minutes, phosphoric acid is added for neutralization, and magnesium silicate is added to remove salt substances to obtain a modified hyperbranched polyether, and the amount of potassium hydroxide is 0.3% of the total mass of the reactants added.
[0047] The modified MoS2 / ZIF-8 composite material was prepared by the following steps:
[0048] Step B1, 0.9 g zinc nitrate hexahydrate and 1.95 g 2-methylimidazole were added to 30 mL methanol and mixed evenly, respectively recorded as solution 1 and solution 2, then solution 1 and solution 2 were mixed and stirred for 2 h, ultrasonicated for 1 h, transferred to an autoclave, reacted at 90 ° C for 7 h, cooled to room temperature, centrifuged, washed, and dried to obtain ZIF-8;
[0049] Step B2, 2 g ZIF-8, 1 g ammonium molybdate and 3 g thiourea were added to deionized water and stirred evenly, then transferred to an autoclave, reacted at 200 ° C for 10 h, cooled to room temperature, centrifuged, washed, dried, collected the product, and calcined at 700 ° C for 3 h to obtain a MoS2 / ZIF-8 composite material;
[0050] Step B3, add 1g of MoS2 / ZIF-8 composite material to a mixture of 50g of deionized water and 10g of ethanol, adjust the pH of the system to 4, ultrasonically treat for 30min, then add 0.04g of γ-aminopropyltriethoxysilane, condense and reflux at 60°C for 6h, after the reaction is completed, reduce pressure and filter, wash and dry to obtain a modified MoS2 / ZIF-8 composite material.
[0051] Embodiment 4, a method for preparing a durable seawater desalination membrane, comprising the following steps:
[0052] Step S1, after mixing 15wt% polysulfone, 2wt% modified MoS2 / ZIF-8 composite material prepared in Example 1 and 83wt% N,N-dimethylformamide for 10min, adjusting the system temperature to 120°C and heating and stirring for 5h, and then standing for 24h to form a casting solution, and then evenly coating the casting solution on a non-woven fabric, and then immersing it in water to obtain a base film;
[0053] Step S2, immersing the base membrane in the aqueous solution and the oil phase solution in turn for 1.5 minutes each, and then rinsing with deionized water for 10 minutes to obtain a seawater desalination membrane, the aqueous solution is prepared by mixing 2wt% of m-phenylenediamine, 0.5wt% of the modified hyperbranched polyether prepared in Example 1, 0.1wt% of the modified MoS2 / ZIF-8 composite material prepared in Example 1, 2wt% of isopropanol, 0.01wt% of sodium hydroxide, and the remainder is deionized water; the oil phase solution is prepared by mixing 0.15wt% of trimesoyl chloride, 1wt% of toluene, 5wt% of anisole, and the remainder is deionized water.
[0054] Embodiment 5, a method for preparing a durable seawater desalination membrane, comprising the following steps:
[0055] Step S1, after mixing and stirring 18wt% polysulfone, 3wt% modified MoS2 / ZIF-8 composite material prepared in Example 2 and 79wt% N,N-dimethylformamide for 20min, adjusting the system temperature to 125°C and heating and stirring for 8h, and then standing for 24h to form a casting solution, and then evenly coating the casting solution on a non-woven fabric, and then immersing it in water to obtain a base film;
[0056] Step S2, immersing the base membrane in the aqueous solution and the oil phase solution in turn for 2 minutes each, and then rinsing with deionized water for 10 minutes to obtain a seawater desalination membrane, the aqueous solution is 2.5wt% of m-phenylenediamine, 0.7wt% of the modified hyperbranched polyether prepared in Example 2, 0.3wt% of the modified MoS2 / ZIF-8 composite material prepared in Example 2, 3wt% of isopropanol, 0.03wt% of sodium hydroxide, and the remainder is deionized water mixed and stirred, and the oil phase solution is 0.25wt% of trimesoyl chloride, 2wt% of toluene, 7wt% of anisole, and the remainder is deionized water mixed and stirred.
[0057] Embodiment 6, a method for preparing a durable seawater desalination membrane, comprising the following steps:
[0058] Step S1, after mixing 20wt% polysulfone, 4wt% modified MoS2 / ZIF-8 composite material prepared in Example 3 and 76wt% N,N-dimethylformamide for 30min, adjusting the system temperature to 130°C, heating and stirring for 10h, and then standing for 24h to form a casting solution, and then evenly coating the casting solution on a non-woven fabric, and then immersing it in water to obtain a base film;
[0059] Step S2, immersing the base membrane in the aqueous solution and the oil phase solution in turn for 2.5 minutes each, and then rinsing with deionized water for 10 minutes to obtain a seawater desalination membrane, the aqueous solution is 3wt% of m-phenylenediamine, 1wt% of the modified hyperbranched polyether prepared in Example 3, 0.5wt% of the modified MoS2 / ZIF-8 composite material prepared in Example 3, 5wt% of isopropanol, 0.05wt% of sodium hydroxide, and the remainder is deionized water mixed and stirred, and the oil phase solution is 0.3wt% of trimesoyl chloride, 3wt% of toluene, 8wt% of anisole, and the remainder is deionized water mixed and stirred.
[0060] Comparative Example 1: This comparative example is a seawater desalination membrane. The difference from Example 6 is that an equal amount of modified ZIF-8 is used to replace the modified MoS2 / ZIF-8 composite material prepared in Example 3, and the rest are the same; wherein, the modified ZIF-8 is prepared by surface modification of ZIF-8 with γ-aminopropyltriethoxysilane.
[0061] Comparative Example 2: This comparative example is a seawater desalination membrane. The difference from Example 6 is that an equal amount of m-phenylenediamine is used to replace the modified hyperbranched polyether prepared in Example 3, and the rest are the same;
[0062] The desalination membranes prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to desalination tests on a membrane test bench, and the water flux and desalination rate after the membranes were operated for 30 minutes were measured. The results are shown in the following table (test conditions: operating pressure of 800 psi, NaCl original aqueous solution concentration of 32 g / L, solution temperature of 25°C, pH value of 6.5-7.5); the membranes (the desalination membranes prepared in Examples 4-6 and Comparative Examples 1-2) were immersed in bacterial culture solutions (Escherichia coli and Staphylococcus aureus, CFU=10 6 / mL) and cultured at 37°C for 24 hours. The percentage of bacterial reduction R was calculated according to R%=100×(AB) / A (A is the number of bacteria at time 0, B is the number of bacteria after 24 hours):
[0063] The test results are shown in the following table:
[0064]
[0065] It can be seen from the above table that the seawater desalination membrane prepared by the present invention has a high water flux, an excellent desalination rate and good durability.
[0066] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a durable seawater desalination membrane, characterized in that: The following steps are involved: Step S1, after mixing and stirring 15-20wt% polysulfone, 2-4wt% modified MoS2 / ZIF-8 composite material and 70-90wt% N,N-dimethylformamide for 10-30min, adjusting the system temperature to 120-130°C, heating and stirring for 5-10h, and then standing for 24h to form a casting solution, and then evenly coating the casting solution on a non-woven fabric, and then immersing it in water to obtain a base film; Step S2, immersing the base membrane in the aqueous solution and the oil phase solution in turn for 1.5-2.5 minutes each, and then rinsing with deionized water for 10 minutes to obtain a seawater desalination membrane; In step S2, the aqueous phase solution is prepared by mixing 2-3wt% of m-phenylenediamine, 0.5-1wt% of modified hyperbranched polyether, 0.1-0.5wt% of modified MoS2 / ZIF-8 composite material, 2-5wt% of isopropanol, 0.01-0.05wt% of sodium hydroxide and deionized water, and the oil phase solution is prepared by mixing 0.15-0.3wt% of trimesoyl chloride, 1-3wt% of toluene, 5-8wt% of anisole and deionized water; The modified MoS2 / ZIF-8 composite material is prepared by the following steps: Step B1, zinc nitrate hexahydrate and 2-methylimidazole were added to 30 mL of methanol and mixed evenly, respectively recorded as solution 1 and solution 2, then solution 1 and solution 2 were mixed and stirred for 2 h, ultrasonicated for 1 h, transferred to an autoclave, reacted at 90 ° C for 5-7 h, cooled to room temperature, centrifuged, washed, and dried to obtain ZIF-8; Step B2, adding ZIF-8, ammonium molybdate and thiourea into deionized water and stirring evenly, transferring to an autoclave, reacting at 150-200°C for 5-10h, cooling to room temperature, centrifuging, washing, drying, collecting the product, and calcining at 500-700°C for 1-3h to obtain a MoS2 / ZIF-8 composite material; Step B3, add MoS2 / ZIF-8 composite material to the mixed solution of deionized water and ethanol, adjust the system pH to 4, ultrasonically treat for 30 minutes, then add γ-aminopropyltriethoxysilane, condense and reflux at 40-60°C for 6 hours, and after the reaction is completed, reduce pressure and filter, wash and dry to obtain the modified MoS2 / ZIF-8 composite material; The modified hyperbranched polyether is prepared by the following steps: Step A1, adding pentaerythritol and potassium hydroxide into a reactor, raising the system temperature to 90-110° C. under stirring conditions, then introducing nitrogen, continuing to raise the temperature to 120-130° C., adding propylene oxide and stirring to react for 2-3 hours, after the reaction is completed, adding ethylene oxide, and controlling the system temperature to 110-120° C. and continuing to stir and react for 4-5 hours, after the reaction is completed, a hyperbranched polyether is obtained; Step A2, adding the hyperbranched polyether and ethyl 2-aminoacetate into a reactor and stirring to mix evenly, then adding potassium hydroxide and stirring evenly, introducing nitrogen, and raising the system temperature to 125-135 ° C. to react for 3-4 hours, and then raising the system temperature to 140-150 ° C., and continue to react for 4-5 hours. After the reaction is completed, maintain the system temperature, vacuum treat for 40-60 minutes, add phosphoric acid for neutralization, and add magnesium silicate to remove salt substances to obtain a modified hyperbranched polyether.
2. The method for preparing a durable seawater desalination membrane according to claim 1, characterized in that: In step A1, the usage ratio of pentaerythritol, potassium hydroxide, propylene oxide and ethylene oxide is 0.01-0.03 mol: 0.05-0.15 g: 0.04-0.12 mol: 0.16-0.48 mol.
3. The method for preparing a durable seawater desalination membrane according to claim 1, characterized in that: In step A2, the molar ratio of the hyperbranched polyether to ethyl 2-aminoacetate is 0.15-0.3:0.1-0.12, and the amount of potassium hydroxide used is 0.2-0.3% of the total mass of the reactants added.
4. The method for preparing a durable seawater desalination membrane according to claim 1, characterized in that: In step B1, the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 0.3-0.9:0.65-1.
95.
5. The method for preparing a durable seawater desalination membrane according to claim 1, characterized in that: In step B2, the mass ratio of ZIF-8, ammonium molybdate and thiourea is 0.5-2:1:1-3.
6. The method for preparing a durable seawater desalination membrane according to claim 1, characterized in that: In step B3, the mass ratio of the MoS2 / ZIF-8 composite material, γ-aminopropyltriethoxysilane, deionized water and ethanol is 1:0.0025-0.04:50:
10.
7. A durable seawater desalination membrane prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Metal-Organic Frameworks ZIF-Based Polyamide Mixed Matrix Membranes and Preparation Method Thereof
AU2020104003A4
Polymer composite membrane for in-situ growth of MOF (Metal Organic Framework) middle layer in low-temperature water phase as well as preparation and application
CN114515517A
Cited By
Reverse osmosis membrane based on perfluorosilane modified ultrafiltration membrane as well as preparation method and application of reverse osmosis membrane
CN121588648A
A reverse osmosis membrane based on perfluorosilane modified ultrafiltration membrane, its preparation method and application
CN121588648B